2019
DOI: 10.1007/s00572-019-00899-x
|View full text |Cite
|
Sign up to set email alerts
|

First record of North American fungus Rhizopogon pseudoroseolus in Australia and prediction of its occurrence based on climatic niche and symbiotic partner preferences

Abstract: In 2017 a North American fungus, Rhizopogon pseudoroseolus (Boletales, Basidiomycota), formerly known in Oceania as only occurring in New Zealand, was found for the first time in South Australia. The morphological identification of collected specimens was confirmed using an internal transcribed spacer barcoding approach. In this study, the biogeography of R. pseudoroseolus is also presented, based on sporocarp and ectomycorrhiza records. Species distribution modeling implemented in MaxEnt was used to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…2100-8200 (vs 2800-5800), and precipitation seasonality (bio15) values up to 80 mm (vs up to 40 mm). The current potential range of C. archeri in Europe is much broader than its actual occurrence as revealed by the occurrence data (Table 5), further confirming our previous studies showing that the realized niches of nonnative fungi are smaller than the predicted niches (Pietras et al 2018;Banasiak et al 2019;Pietras 2019;Pietras and Kolanowska 2019). Our model indicated that numerous suitable habitats are located in Europe, e.g., in the British Isles, Apennine Peninsula, Carpathians, Balkans, and Eastern Europe, where no GBIF records of the fungus are currently available (GBIF.org, 26 October 2018b).…”
Section: Where Did C Archeri Originate?supporting
confidence: 87%
See 3 more Smart Citations
“…2100-8200 (vs 2800-5800), and precipitation seasonality (bio15) values up to 80 mm (vs up to 40 mm). The current potential range of C. archeri in Europe is much broader than its actual occurrence as revealed by the occurrence data (Table 5), further confirming our previous studies showing that the realized niches of nonnative fungi are smaller than the predicted niches (Pietras et al 2018;Banasiak et al 2019;Pietras 2019;Pietras and Kolanowska 2019). Our model indicated that numerous suitable habitats are located in Europe, e.g., in the British Isles, Apennine Peninsula, Carpathians, Balkans, and Eastern Europe, where no GBIF records of the fungus are currently available (GBIF.org, 26 October 2018b).…”
Section: Where Did C Archeri Originate?supporting
confidence: 87%
“…Species distribution models are rather infrequently used in research on nonpathogenic fungi. Thus far, analyses of the future distributions of these organisms have been implemented in biogeographical studies on Boletales in North America (Pietras et al 2018;Banasiak et al 2019;Pietras 2019;Pietras and Kolanowska 2019) and on rare wood-inhabiting saprotrophs restricted to European boreal forests (Kujawska et al 2021). Therefore, studies of C. archeri and its introduction outside of its native range contribute to the discussion on the occurrence of nonpathogenic fungi outside their natural habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important ectomycorizal fungi are sulloid fungi.The truffle-like Suillus and Rhizopogon genera are the largest ectomicorizal groups [23]. R. roseolus is a fungi species that establishes an ectomycorizal relationship with the Pinaceae family [24].…”
Section: Introductionmentioning
confidence: 99%